Rehabilitation patients of cerebral stroke - L. B. Novikova; K. M. Sharapova (Лечащий Врач, 2024)
Background. Predicting the success of rehabilitation in patients who have suffered an ischemic stroke (IS) is determined by factors of rehabilitation potential (RP). Assessment of RP is necessary to develop an effective rehabilitation program and predict the degree of restoration of impaired functions.Objective. The purpose of the study is to evaluate the effectiveness of rehabilitation in patients who have undergone IS.Materials and methods. A prospective study was carried out on 177 patients who were treated in the neurological department for patients with acute cerebrovascular accident and the neurorehabilitation department of the State Budgetary Healthcare Institution of the Republic of Bashkortostan of the Clinical Emergency Hospital in Ufa. All patients underwent clinical neurological, neuroimaging, laboratory and instrumental studies. The NIHSS, Rankin, Rivermead, Montreal Cognitive Function Scale, Hospital Anxiety and Depression Scale, A. M. questionnaire were used. Wein, T. Ehlers test and A. M. Schubert technique. The assessment of the RP was carried out using the analysis of data from the "Rehabilitation Sheet".Results. The majority of patients with IS were diagnosed with cognitive, anxiety-depressive disorders, and dysfunction of the autonomic nervous system. During treatment, the number of patients with mild neurological deficits, mild disabilities and an average level of mobility increased significantly. Based on a combination of factors, 74% of patients had medium and high levels of RP. In our study, according to the T. Ehlers test, 82.9% of patients before treatment had a medium to high degree of motivation to succeed. Conclusion. An integrated and individualized approach to the correction of various pathological disorders in patients who have undergone IS, taking into account RP, is the key to the effectiveness of restorative treatment at the stages of rehabilitation.